Lipopolysacharide Rapidly and Completely Suppresses AgRP Neuron-Mediated Food Intake in Male Mice - Liu, Yang (Endocrinology, 2016)
Although Agouti-related peptide (AgRP) neurons play a key role in the regulation of food intake, their contribution to the anorexia caused by proinflammatory insults has yet to be identified. Using a combination of neuroanatomical and pharmacogenetics experiments, this study sought to investigate the importance of AgRP neurons and downstream targets in the anorexia caused by the peripheral administration of a moderate dose of lipopolysaccharide (LPS) (100 μg/kg, ip). First, in the C57/Bl6 mouse, we demonstrated that LPS induced c-fos in select AgRP-innervated brain sites involved in feeding but not in any arcuate proopiomelanocortin neurons. Double immunohistochemistry further showed that LPS selectively induced c-Fos in a large subset of melanocortin 4 receptor-expressing neurons in the lateral parabrachial nucleus. Secondly, we used pharmacogenetics to stimulate the activity of AgRP neurons during the course of LPS-induced anorexia. In AgRP-Cre mice expressing the designer receptor hM3Dq-Gq only in AgRP neurons, the administration of the designer drug clozapine-N-oxide (CNO) induced robust food intake. Strikingly, CNO-mediated food intake was rapidly and completely blunted by the coadministration of LPS. Neuroanatomical experiments further indicated that LPS did not interfere with the ability of CNO to stimulate c-Fos in AgRP neurons. In summary, our findings combined together support the view that the stimulation of select AgRP-innervated brain sites and target neurons, rather than the inhibition of AgRP neurons themselves, is likely to contribute to the rapid suppression of food intake observed during acute bacterial endotoxemia.